Spa And Reflexology Services Ordering Information System - Rinaldy, Rio (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Booking spa and reflexology services online is increasingly popular in this digital era. However, there are still many spa and reflexology entrepreneurs who do not have an online booking system. This can cause crowds and inconvenience for customers. Therefore, it is necessary to develop a spa and reflexology service booking information system to provide convenience and comfort for customers. This research aims to develop an effective and efficient spa and reflexology service booking information system. This system is expected to provide convenience and comfort for customers in ordering spa and reflexology services. This research uses an information system development method with a waterfall approach. The stages include requirements analysis, system design, system implementation, system testing, and system maintenance. Data is collected through direct observation at the spa and reflexology place which is the object of research, interviews with customers, and literature studies related to the development of service booking information systems. Data obtained from data collection techniques are analyzed using descriptive analysis and content analysis. The results showed that the spa and reflexology service booking information system developed successfully provided convenience and comfort for customers in ordering services. In addition, this system also helps managers in managing booking schedules and optimizing services to customers.